Does Indonesia’s Job Creation Law Promote Decent Work? An Ex Post Regulatory Impact Analysis of Employment Reform and SDG 8 Alignment - Mohammad Arif; Rizki Ramadani; Aan Aswari (Vifada Assumption Journal of Law, 2025)
Purpose: This study examines whether Indonesia’s Job Creation Law promotes decent work under SDG 8 through an ex post RIA framework. Research Design and Methodology: Using juridical-normative legal research supported by secondary labour data, this study analyses statutory provisions, implementing regulations, Constitutional Court jurisprudence, policy reports, labour statistics, and academic literature. The analysis compares the law’s objectives of regulatory simplification, labour market flexibility, and job creation with five decent work indicators: productive employment opportunities, job stability and security, adequate earnings and fair working conditions, social protection, and labour rights and social dialogue. Findings and Discussion: The findings show that the law has contributed to formal regulatory simplification and quantitative employment growth. However, its alignment with SDG 8 remains limited because expanded fixed-term contracts, outsourcing flexibility, reduced termination costs, wage pressures, selective job loss protection, and weak social dialogue increase the risk of precarious work. Implications: This study recommends institutionalising SDG 8-based ex post RIA so that future labour law reforms assess not only job numbers, but also job quality, legal protection, social security, and substantive worker rights.